Effects of cations in sulfate on the thaumasite form of sulfate attack of cementitious materials. (30th December 2019) - Luo, Yaoling; Zhou, Shuai; Wang, Chong; Fang, Zheng
Highlight: The degradation process of the TSA is studied in the sulfate solution. The effect of cations in the sulfate on the TSA has been investigated. The influence of mixed cations has been considered. The relative corrosivity of cations was: Mg 2+  > Ca 2+  > Na + . Abstract: The thaumasite form of sulfate attack (TSA) of cement-based materials is a severe threat. There is little research on the effect of cations in the sulfate on the TSA, especially the mixed cations. The effects of six conditions, namely, Na2 SO4 full immersion, MgSO4 full immersion, CaSO4 full immersion, Na2 SO4 & MgSO4 full immersion, Na2 SO4 & CaSO4 full immersion and MgSO4 & CaSO4 full immersion, on the TSA were studied by the observed degradation grades, mass loss, Raman analysis and X-ray diffraction (XRD). Results show that the degradation grade, degradation rate and degradation products are influenced by cations greatly.